Description of tadpoles of the frogs Heterixalus tricolor, H. carbonei and H. luteostriatus (Anura: Hyperoliidae) from western Madagascar - Griep, Stine; Glos, Julian (Zootaxa, 2020)
The genus Heterixalus is endemic to Madagascar. It contains eleven species of small to medium-sized tree frogs that typically inhabit open areas like swamps and rice fields. We describe the larval stages of three sympatric species that occur in western Madagascar: H. tricolor, H. carbonei, and H. luteostriatus. Similar to other species of this genus, the tadpoles of these species have a depressed, ovoid body-form and a generalized oral disc. The labial tooth row formula is 1/3(1). Examined phenotypes differed marginally between species. Compared to H. tricolor and H. carbonei, H. luteostriatus showed fewer cusps on the fork-like labial teeth, a lower ventral fin, and a shorter tail. The high morphological resemblance implicates an ecological similarity between species. Highly overlapping niches raise questions on how species co-occur.